2015
DOI: 10.1007/s00442-014-3212-3
|View full text |Cite
|
Sign up to set email alerts
|

Measuring individuality in habitat use across complex landscapes: approaches, constraints, and implications for assessing resource specialization

Abstract: Many mobile marine species are presumed to utilize a broad spectrum of habitats, but this seemingly generalist life history may arise from conspecifics specializing on distinct habitat alternatives to exploit foraging, resting/refuge, or reproductive opportunities. We acoustically tagged 34 red drum, and mapped sand, seagrass, marsh, or oyster (across discrete landscape contexts) use by each uniquely coded individual. Using 144,000 acoustic detections, we recorded differences in habitat use among red drum: pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 35 publications
0
51
0
Order By: Relevance
“…This result may be related to the low availability of urban dumps in the area covered by GPS-tracked individuals (Navarro et al 2016). Although all GPS-tracked yellow-legged gulls could potentially exploit all available habitats, based on PSi values -a metric to test individual specialization (Bolnick et al 2002, Fodrie et al 2015) -we found clear differences in habitat use among individuals within the population. These results are coherent with the prediction that some generalist or opportunistic species are composed of ecologically heterogeneous individuals that repeatedly differ in behaviour and use of different subsets of available resources (Bolnick et al 2002, Bearhop et al 2004, Bell et al 2009).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…This result may be related to the low availability of urban dumps in the area covered by GPS-tracked individuals (Navarro et al 2016). Although all GPS-tracked yellow-legged gulls could potentially exploit all available habitats, based on PSi values -a metric to test individual specialization (Bolnick et al 2002, Fodrie et al 2015) -we found clear differences in habitat use among individuals within the population. These results are coherent with the prediction that some generalist or opportunistic species are composed of ecologically heterogeneous individuals that repeatedly differ in behaviour and use of different subsets of available resources (Bolnick et al 2002, Bearhop et al 2004, Bell et al 2009).…”
Section: Discussionmentioning
confidence: 75%
“…Individual specialization in habitat use by each tracked yellow-legged gull was quantified following Bolnick et al (2002) and Fodrie et al (2015). Specifically, we calculated the proportional habitat use by each yellow-legged gull as the number of habitatspecific positions divided by the total number of GPS positions recorded during the entire tracking period for a particular individual.…”
Section: Individual Specialization and Individual Spatial Segregationmentioning
confidence: 99%
See 1 more Smart Citation
“…We used complementary bio-logging and stable isotope analysis, coupled with morphometric measurements to: (1) describe their inter-individual variation in morphology, spatial use and dive behaviour; (2) quantify their intra-individual variation in foraging behaviour; (3) investigate the links between consistency in foraging behaviour, distances travelled and body condition; and (4) describe their interindividual variation in feeding ecology, and determine if dietary specialisations exist and are maintained outside of the breeding season. We predicted that: (1) individuals would differ greatly in foraging metrics, as gentoo penguin diet and behaviour are known to vary among colonies and between individuals of the same colonies, and that such variation would be attributed to differences in body mass, which influences dive depth (Lescroël et al 2004, Lescroël & Bost 2005, Cook et al 2013, Polito et al 2015, Camprasse et al 2017; (2) dietary and behavioural consistency would be detected, as populations usually considered generalists are increasingly shown to be composed of individual specialists (Woo et al 2008, Araújo et al 2011, Loxdale et al 2011, Layman & Allgeier 2012, Fodrie et al 2015; and (3) individuals displaying higher consistency in foraging behaviour would travel shorter distances and have higher body condition, as such consistency is thought to allow individuals to forage more efficiently (Bolnick et al 2003, Estes et al 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Individual specialists have been defined as 'individuals whose niche is substantially narrower than their population's niche for reasons not attributable to their sex, age or discrete morphological group' (Bolnick et al 2003, p. 3). Even populations usually thought to be generalists can actually be composed of individual specialists, referred to as Type 'B' generalists (individuals each specialising on a different but narrow range of food types) as op posed to Type 'A' generalists (individuals all taking a wide range of food types) (Araújo et al 2011, Loxdale et al 2011, Layman & Allgeier 2012, Fodrie et al 2015.…”
Section: Introductionmentioning
confidence: 99%